Stability Analysis of Jointed Rock Cutting Slope Based on Discrete Element Method - Wei Zhu; Liang Gao; Yingai Zhao; Chao Yang; Wei Sun; Pengqiang Yu (Advances in Civil Engineering)
The joints in the rock mass are essential for the stability of rocky slopes, and the destabilization damage of the slope is often directly related to the joints. In this study, in order to reveal the instability process and mechanism of rock slopes from a microscale perspective, the DEM simulations for rocky slopes of the K88 + 400∼K88 + 540 section of Zhongkai Expressway are carried out considering the influence of joints. Based on the findings of the on-site jointed structural surfaces, a rocky slope model containing two sets of intermittent joints was constructed, and the linear parallel bond model and the smooth joint model are used to characterize the rock body and joints, respectively. The evolution of microfracture, contact force chain, and particle displacement are analyzed to explore the micromechanism of slope instability. Finally, the triple reinforcement scheme of anchor cable frame and grass planting is proposed. The research results can provide a reference for stability analysis and reinforcement of similar rocky slope projects.